2012
DOI: 10.1017/s1431927612001274
|View full text |Cite
|
Sign up to set email alerts
|

Strain Measurement in Semiconductor Heterostructures by Scanning Transmission Electron Microscopy

Abstract: This article deals with the measurement of strain in semiconductor heterostructures from convergent beam electron diffraction patterns. In particular, three different algorithms in the field of~circular! pattern recognition are presented that are able to detect diffracted disc positions accurately, from which the strain in growth direction is calculated. Although the three approaches are very different as one is based on edge detection, one on rotational averages, and one on cross correlation with masks, it is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…Due to the incredibly large size of the datasets obtained, both in file size and number of disk positions to be measured, only the fastest algorithms are considered. For example, while other authors have used edge detection via Canny or Prewitt filters followed by circle fitting to find the center of the disk [8], that approach is very computationally intensive, requiring several iterative steps per disk in order to resolve a measurement with subpixel accuracy. Additionally, that method relies on accurate filter thresholds which can vary with the type of diffracted disk structure observed, decreasing general robustness and ease of use.…”
Section: Methods For Determining Diffraction Disk Positionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the incredibly large size of the datasets obtained, both in file size and number of disk positions to be measured, only the fastest algorithms are considered. For example, while other authors have used edge detection via Canny or Prewitt filters followed by circle fitting to find the center of the disk [8], that approach is very computationally intensive, requiring several iterative steps per disk in order to resolve a measurement with subpixel accuracy. Additionally, that method relies on accurate filter thresholds which can vary with the type of diffracted disk structure observed, decreasing general robustness and ease of use.…”
Section: Methods For Determining Diffraction Disk Positionsmentioning
confidence: 99%
“…Radial gradient maximization is another method used [21,8,22], in which concentric circles or ellipses are placed around an estimated disk center and their rotational averages are calculated. Since most disks have sharp edges, when the difference between the rotational average of concentric shapes are a maximum, the concentric shapes are properly placed around the center of the disk.…”
Section: Methods For Determining Diffraction Disk Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread in the local strain corresponds to around 0.3%. Taking into account that the precision of the nanodiffraction strain mapping technique is around 0.1%, 11 it can be concluded that this spread is considerably larger than the statistical error. The agreement of the mean local stress with the global stress demonstrates the applicability of the presented in situ strain mapping method and the ability to measure sample stresses without the need of a quantitative deformation holder and independent of the sample geometry.…”
mentioning
confidence: 98%
“…10 Alternatively, the precise measurement of diffracted peak positions allows for the determination of local strain in the material using Bragg's law. Nanodiffraction strain mapping is not only a very accurate technique 11 but also very robust; 12 while techniques based on high-resolution electron microscopy or electron holography have stringent sample requirements such as perfect zone-axis or the presence of an unstrained reference region in the field of view, nanodiffraction strain mapping is able to measure strain as long as the corresponding diffracted spots are visible and is therefore well suited for in situ deformation where some bending is inevitable. Nanodiffraction strain mapping is largely immune to dynamical scattering effects from large sample thicknesses because the measurement is only sensitive to the position of diffraction discs, not the details of fine intensity structure within the discs.…”
mentioning
confidence: 99%